Buforin IIb induces androgen-independent prostate cancer cells apoptosis though p53 pathway in vitro. (October 2019) - Han, Yangyang; Lu, Ming; Zhou, Jinsong
Abstract: Prostate cancer (PCa) is one of the most common male cancer types, androgen-independent prostate cancer possesses poor prognosis. Buforin IIb, an attractive antibacterial peptide derived from histone H2A, showed selective cytotoxicity against most cancer cell lines. However, the molecular mechanism of buforin IIb on prostate cancer cell has still not been determined. In this study, we found buforin IIb significantly inhibited the prostate cancer cells proliferation, Furthermore, buforin IIb–induced cell apoptosis through downregulation of pro-caspase 3/8/9, poly (ADP-ribose) polymerase PARP and anti-apoptotic Bcl-2 and upregulation of pro-apoptotic Bax. In addition, buforin IIb increased the expression of tumor suppressor p53 and its target genes - p21, fas, noxa and puma. The cytotoxicity of buforin IIb on PC-3 and Du-145 cells is decreased by p53 knockdown. In conclusion, our results indicated that buforin IIb induced PC-3 and Du-145 cell apoptosis and could be considered as a potential drug for prostate cancer. Highlights: Buforin IIb demonstrated to inhibit androgen-independent prostate cancer cell proliferation. Buforin IIb induced androgen-independent prostate cancer cell apoptosis. Buforin IIb exerted an inhibitory effect through modulating the protein level of p53–Bcl-2 family protein.